Integration of ICT-Based Career Skills Program in Islamic Religious Education: Case Study of MAN 2 Cirebon City - Nakhma'ussolikhah; Hara Permana; Sulistianingsih; Muhammad Lutfi Anshori; Putri Salma Kirana; Muhammad Yoga Nugraha (Kolej PERMATA Insan, 2025)
International Conference And Innovation On Education, Science & Technology (ICIEST 2025) “Fostering Innovation And Creativity Through Education, Science & Technology” 21st June 2025 Editor : Hatika Kaco, Diani Mardiana Mat Zin, Fadzidah Mohd Idris, Siti Munirah Mohd Nurhidaya Mohamad Jan, Nor Atirah Izzah Zulkefli, Nadiah Suboh Organised by : Education & Advanced Sustainability (EdAS) unit, Kolej PERMATA Insan, Universiti Sains Islam Malaysia